Raman characterization of terrestrial analogs from the AMADEE‐18 astronaut simulated mission using the ExoMars RLS simulator: Implications for Mars. (9th November 2020) - Lalla, Emmanuel Alexis; Konstantinidis, Menelaos; Lopez‐Reyes, Guillermo; Daly, Michael G.; Veneranda, Marco; Manrique, José A.; Groemer, Gernot; Vago, Jorge L.; Rull, Fernando
Abstract: Between February 1 and February 28, 2018, the Austrian Space Forum, in cooperation with research teams from 25 nations, conducted the AMADEE‐18 mission—a human‐robotic Mars expedition simulation in the Dhofar region in the Sultanate of Oman. As a part of the AMADEE‐18 simulated Mars human exploration mission, the Remote Science Support team investigated the Dhofar area (Oman) to qualify it as a potential Mars analog site. The motivation of this research was to study and register selected samples collected by the analog astronauts during the AMADEE‐18 mission with the European Space Agency (ESA) ExoMars Raman Laser Spectrometer (RLS) simulator, compare the results with standard laboratory measurements, and establish the implication of the results to the future ESA ExoMars mission. The Raman measurements identified minerals such as carbonates (calcite and dolomite), feldspar and plagioclase (albite, anorthite, orthoclase, and sanidine), Fe‐oxides (goethite, hematite, and magnetite), and Ti‐oxide (anatase), each relevant to planetary exploration. As we have presented here, Raman spectroscopy is a powerful tool for detecting the presence of organic molecules, particularly by analyzing the principal vibration of CC and CH bonds. It has also been shown that portable Raman spectroscopy is a relevant tool for in situ field studies such as those conducted during extra‐vehicular activities (EVA) in simulated missions like the AMADEE‐18 and the future AMADEE‐2020 campaign. Abstract : The AMADEE‐18 mission, a simulated crewed expedition to Mars, collected Martian‐analog samples from the Dofar area in Oman that have been analyzed by Raman spectroscopy with the RLS ExoMars simulator. The results show a great potential of detection and identification of minerals and organics, establishing Raman spectroscopy as a key technique for future robotic or crewed planetary exploration missions.